2009
DOI: 10.3390/rs1030418
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Mexico’s Informal Economy and Remittances Using Nighttime Imagery

Abstract: Accurate estimates of the magnitude and spatial distribution of both formal and informal economic activity have many useful applications. Developing alternative methods for making estimates of these economic activities may prove to be useful when other measures are of suspect accuracy or unavailable. This research explores the potential for estimating the formal and informal economy for Mexico using known relationships between the spatial patterns of nighttime satellite imagery and economic activity in the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(80 citation statements)
references
References 31 publications
(30 reference statements)
1
72
0
5
Order By: Relevance
“…A number of studies have indicated that the nighttime light has a very high correlation with the national and regional economic volume [11,12]. Compared to the census approach, the mapping of nighttime light can help to investigate the economics on a large scale with very low cost; thus, the nighttime light imagery has been used to investigate the regional economics in many countries [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have indicated that the nighttime light has a very high correlation with the national and regional economic volume [11,12]. Compared to the census approach, the mapping of nighttime light can help to investigate the economics on a large scale with very low cost; thus, the nighttime light imagery has been used to investigate the regional economics in many countries [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Much of this research uses land cover or use maps derived from remotely sensed images and correlate these with economic growth and stability. Geographers were the first to utilize DMSP OLS to examine economic activity [93]. While most existing studies have emphasized associations at high levels of data aggregation such as countries, increasingly applications at the subnational level emerge with efforts led by economists [160,161].…”
Section: Social and Economic Modelingmentioning
confidence: 99%
“…At sub-national scales economic nighttime data lead to rougher estimates of GDP, but offer clues to the magnitude of the informal economy (e.g., North Korea, Mexico, and India) [92,93]. A time series analysis of annual DMSP OLS composite data products was used to estimate changes in economic growth (change in GDP from year to year) [94].…”
Section: Social and Economic Indicesmentioning
confidence: 99%
“…Considering the close relationship between NSL and urbanization [63], population [70], economy [71], energy consumption [72], etc., NSL is further found to correlate well with the anthropogenic heat flux density [44,47]. This study does not try to calculate the anthropogenic heat with NSL, but attempts to use NSL to provide relevant information on the anthropogenic heat for better Ta estimation over a large area.…”
Section: Nighttime Light Predictor Independence and Coefficient Dynmentioning
confidence: 99%